Thorough investigation on the high-temperature polymorphism of dipentyl-perylenediimide: thermal expansion vs. polymorphic transition. Issue 20 (12th May 2022) - Marin, Francesco; Tombolesi, Serena; Salzillo, Tommaso; Yaffe, Omer; Maini, Lucia
Abstract : An extensive study on polymorphs, crystal structures and thermal expansion of PDI-C5 Abstract : N, N ′-Dipentyl-3, 4, 9, 10-perylendiimide (PDI-C5 ) is an organic semiconducting material which has been extensively investigated as model compound for its optoelectronic properties. It is known to be highly thermally stable, that it exhibits solid-state transitions with temperature and that thermal treatments lead to an improvement in its performance in devices. Here we report a full thermal characterization of PDI-C5 by combination of differential scanning calorimetry, variable temperature X-ray diffraction, hot stage microscopy, and variable temperature Raman spectroscopy. We identified two high temperature polymorphs, form II and form III, which form respectively at 112 °C and at 221 °C and we determined their crystal structure from powder data. Form II is completely reversible upon cooling with low hysteresis, while form III revealed a different thermal behaviour upon cooling depending on the technique and crystal size. The crystal structure features of the different polymorphs are discussed and compared, and we looked into the role of the perylene core and alkyl chains during solid-state transitions. The thermal expansion principal axis of PDI-C5 crystal forms is reported showing that all the reported forms possess negative thermal expansion (X1 ) and large positive thermal expansion (X3 ) which are correlated to thermal behaviour observed.